How will telemedicine change clinical practice in chronic obstructive pulmonary disease?. (6th February 2018) - Vitacca, Michele; Montini, Alessandra; Comini, Laura
Within telehealth there are a number of domains relevant to pulmonary care: telemonitoring, teleassistance, telerehabilitation, teleconsultation and second opinion calls. In the last decade, several studies focusing on the effects of various telemanagement programs for patients with chronic obstructive pulmonary disease (COPD) have been published but with contradictory findings. From the literature, the best telemonitoring outcomes come from programs dedicated to aged and very sick patients, frequent exacerbators with multimorbidity and limited community support; programs using third-generation telemonitoring systems providing constant analytical and decisionmaking support (24 h/day, 7 days/week); countries where strong community links are not available; and zones where telemonitoring and rehabilitation can be delivered directly to the patient's location. In the near future, it is expected that telemedicine will produce changes in work practices, cultural attitudes and organization, which will affect all professional figures involved in the provision of care. The key to optimizing the use of telemonitoring is to correctly identify who the ideal candidates are, at what time they need it, and for how long. The time course of disease progression varies from patient to patient; hence identifying for each patient a 'correct window' for initiating telemonitoring could be the correct solution. In conclusion, as clinicians, we need to identify the specific challenges we face in delivering care, and implement flexible systems that can be customized to individual patients' requirements and adapted to our diverse healthcare contexts.